Chirality Transfer from an Innately Chiral Nanocrystal Core to a Nematic Liquid Crystal: Surface‐Modified Cellulose Nanocrystals. (7th June 2021) - Gonçalves, Diana P. N.; Hegmann, Torsten
Abstract: The vast majority of nanomaterials studied in light of their ability to transmit chirality to or amplify their chirality in a surrounding medium, constitute an achiral core with chirality solely installed at the surface by conjugation or encapsulation with optically active ligands. Here we present the inverse approach focusing on surface‐modified cellulose nanocrystals (CNCs) with core chirality at both the molecular and the morphological level to quantify transmission and amplification of core chirality through space using a host nematic liquid crystal (N‐LC) as reporter. We find that CNCs functionalized at the surface with achiral molecules, structurally related to the N‐LC, exhibit better N‐LC solubility, thereby serving as highly efficient chiral inducers. Moreover, functionalization with chiral molecules only marginally enhances the efficacy of helical distortion in the host N‐LC matrix, indicating the high propensity of CNCs to transfer chirality from an inherently chiral core. Abstract : Cellulose nanocrystals (CNCs), neat or surface‐modified with mesogenic motifs, transmit their inherent structural and morphological chirality to an achiral nematic liquid crystal (N‐LC) elastic medium with a helical twisting power rivaling the most potent organic chiral dopants. The helical pitch, p, of the induced chiral N*‐LC phase is tightened even when CNCs are decorated with achiral molecules bearing structural resemblance to the N‐LC host.